Study on the influence of beam transverse position on the cavity bunch length measurement. (November 2019) - Wang, Qian; Luo, Qing; Sun, Baogen
Abstract: Monopole modes in the resonant cavities are wildly used to obtain the beam current and the bunch length, while dipole modes are used to measure the beam transverse position. It is generally recognized that the monopole modes are independent of the beam transverse offset. In this paper, the influence of beam transverse offset on the bunch length measurement using monopole modes is analyzed. The simulation results show that the relative error of the bunch length measurement is less than 1 % when the beam offset is within 1 mm.